PREVALENCE OF PHOTODERMATOSES IN DISTRICT BUNER, PAKISTAN (Journal of Medical & Health Sciences Review, 2025)
The present research was conducted during August 2021 to August 2022. About four hundred patients of Photodermatoses were investigated. In which five different types of Photodermatoses were reported from the population of district Buner. The  prevalence  of  Photodermatoses  types  are Idopathic  Photodermatoses 301 (Polymorphic light eruption  212, Chronic  Actinic prurig  35, Solar uriticaria 25,  Phototoxic  and  photoallergic  reactions 53, Phorphyrias 16, Photoexacerbated dermatoses 10 and Genodermatoses 20. During  the  present survey,  we  reported  a total of  five  types  of  Photodermatoses  in  which  the  prevalence ratio of Idiopathic Photodermatoses in male is 57.25% and female is 18% higher in male than female, Phototoxic and photoallergic reactions is high in male 8.75% and  in female which is lower 4.5%, Phorophyrias is 2.7% in male and in female is 1.25%, Photoexacerbated dermatoses is 1.25% high in male and lower  in female 0.75%, Genodermatoses is also high in male 3.5% and lower  in female 1.5%. Based on all the facts it can be concluded that due to the presence of variety of Photodermatoses disorders that affect different parts of the skin and are known to alter the quality of life of the individual through the prolonged period of morbidity, including the economic, social, political and educational aspects.